Analisis Model Bisnis pada Eighteen Nineteen Laundry dengan Pendekatan Business Model Canvas - Retno Setyorini; Randy Oktavianry Rey (Jurnal Sekretaris dan Administrasi Bisnis, 2017)
The business model is the primary factor that has a major role in influencing the performance of the business in improving the competitiveness and achieve its goals. One effective tool used in assessing a business model is the business model canvas because it can contribute to the use of business models. Business model canvas focuses on business ideas to create value in the business. This study analyzes the business model on Eighteen Nineteen Laundry. The purpose of this research is to create a new strategy for the business model used by Eighteen Nineteen Laundry. The method used in this research is descriptive and qualitative analysis method by using the in-depth interview in collecting primary data needed during the research process. The result of this research is evaluation and recommendation of business model from Eighteen Nineteen Laundry obtained based on SWOT analysis on each element of business model canvas to improve service quality, marketing activity, infrastructure, financial ability Eighteen Nineteen Laundry. It is hoped that this research can be useful to improve the income stream and can develop the business and be able to compete in the future. Keywords: Business Model, Business Model Canvas Entrepreneurship